COMPARATIVE ANALYS OF CULTURAL CONCEPTS IN ENGLISH AND UZBEK LITERARY TEXTS AND THEIR TRANSLATION - Xoldorova Shahlo Shuhratjon qizi (TADQIQOTLAR, 2025)
Abstract.  This  study  investigates  the  linguistic  and  cultural  dimensions  of English  and  Uzbek  literary  texts  through  a  comparative  lens,  focusing  on  how culturally specific concepts are represented and translated. The research draws on the interdisciplinary  frameworks  of  comparative  literature,  contrastive  linguistics,  and translation studies. Selected novels and short stories by English and Uzbek authors are analyzed to identify common themes, language structures, and translation strategies. The study highlights how cultural and linguistic differences influence literary meaning and how translators manage the challenge of maintaining cultural authenticity while ensuring readability. Findings reveal that certain concepts, such as kinship, hospitality, and spirituality, are deeply rooted in cultural identity and require creative translation strategies,  including  adaptation,  domestication,  and  explanatory  commentary.  The research emphasizes that translation is both an art and a science, involving a balance between fidelity to the source text and sensitivity to the target culture.